DEVELOPMENT OF EFFECTIVE COMPOSITIONS AND TECHNOLOGIES FOR OBTAINING ANTICORROSIVE COMPOSITE INHIBITORY MATERIALS AND COATINGS BASED ON THEM - Shodiev Hamza Ruzicolovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article presents the results of experimental work in the field of research and the development of anti-corrosion inhibiting materials based on selected organinery ingredients from local raw materials and waste of industries and coatings.